Optimization of a large-area grid electrode for negative ion source in fusion neutral beam injector - Jinhong Wang; Yan Wang; Yuwen Yang; Yuming Gu; Yahong Xie; Lizhen Liang; Jianglong Wei (Nuclear Engineering and Technology)
At present, the CRAFT (Comprehensive Research Facility for Fusion Technology) dual-driver negative ion source for neutral beam injection applications has made progress. In order to solve the problem of heat removal function in large-area extraction grid, the multi-physics simulation, manufacturing and testing are carried out. Two simulation conditions before Cs seeding (Je∼350 A/m2, JH-∼50 A/m2) and after sufficient Cs conditioning (Je∼150 A/m2, JH-∼250 A/m2) were considered to evaluate the power load on EG, which peak power density were 11 and 6 MW/m2 respectively and were concentrated on locate near the two aperture rows. This paper mainly studies three designs of minor cooling channels (double bending channels, double straight channels, and single straight channel). First, the grid temperature, thermal stress and thermal deformation are compared with an inlet water rate of 1.21 kg/s at 35 °C, and the channel forming methods and welding types mechanisms are compared. The simulation results show that the thermos-mechanical property of double bending channels is the best, and that of double straight channels is slightly worse. In terms of processing and manufacturing, the yield of double bending channels is lower than double straight channels, and it is easy to leak during the experiment.